Study on dynamic track tension control for high-speed tracked vehicles. (1st October 2019) - Wang, Pingxin; Rui, Xiaoting; Yu, Hailong
Highlights: The derivation of dynamic equation for a mechanical-electrical-hydraulic coupling tracked vehicle system. A DOB-based hybrid controller is developed to keep the driving force constant. The application of constant driving force control strategy to control the dynamic track tension. Abstract: Track tension has a significant impact on the dynamic performance of a track. Maintaining the stability of track tension is conducive to improving the service life of track, meanwhile reducing the risk of peel-off and breakage. The tensioner can adjust the track tension by moving the idler to tighten or loosen the track. However, during the off-road operation, the conventional tensioner is locked, which makes it impossible to adjust the tightness of track in time. The purpose of this paper is to propose a constant hydraulic driving force control method for track vehicles in the driving process. Specifically, for an electro-hydraulic force servo system, the driving force is adjusted in real time and kept constant by a hybrid controller based on a disturbance observer. The dynamic equation of a tracked vehicle is established using transfer matrix method for multibody systems (MSTMM). The control performance is evaluated by the dynamical model together with the analytical model for the electro-hydraulic system. Numerical simulation shows that with the same pre-tension, the average value of dynamic track tension with the tensioner controlled is effectively reduced, and is significantly lower than that with the tensioner locked. Moreover, the stability of track is improved due to the reduced variation range of dynamic tension and track perimeter.